Innovation under financial restrictions - Cornelia Neff (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 1998)
How do financial constraints influence innovative activities of firms? In a two-period model of price competition with differentiated products we first analyze the incentives to innovate when both firms are self-financed. We then assume that one of the firms is financially constrained and therefore has to apply for a bank loan. If Information is asymmetrically distributed between the bank and the firm, the optimal, incentive-compatible debt contract will lead to a reduction of the innovative efforts of the financially restricted firm. On the other side, the unleveraged rival will increase her innovative activities and might even become a monopolist in the second period of competition. If we finally assume that both firms are financially constrained and apply for a loan at their house bank, we can show that Innovation activities are further reduced and overall welfare will decline.
Keywords: D82; G32; L13; O31; 330; competition; Innovation; financial contract; asymmetric Information; Forschung; Innovation; Wettbewerb; Duopol; Unternehmensfinanzierung; Anreizvertrag; Theorie